Effect of the Glucagon-Like Peptide-1 Receptor Agonists Semaglutide and Liraglutide on Kidney Outcomes in Patients With Type 2 Diabetes: Pooled Analysis of SUSTAIN 6 and LEADER. Issue 8 (14th December 2021) - Shaman, Ahmed M.; Bain, Stephen C.; Bakris, George L.; Buse, John B.; Idorn, Thomas; Mahaffey, Kenneth W.; Mann, Johannes F.E.; Nauck, Michael A.; Rasmussen, Søren; Rossing, Peter; Wolthers, Benjamin; Zinman, Bernard; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: We assessed the effect of once-weekly semaglutide and once-daily liraglutide on kidney outcomes in type 2 diabetes. Methods: Pooled (n=12 637) and by-trial data from SUSTAIN 6 (Trial to Evaluate Cardiovascular and Other Long-Term Outcomes With Semaglutide in Subjects With Type 2 Diabetes; n=3297) and LEADER (Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results; n=9340) were assessed for albuminuria change, annual slope of estimated glomerular filtration rate (eGFR) change, and time to persistent eGFR reduction (30%, 40%, 50%, and 57%) from baseline. Results: The median follow-up durations were 2.1 years for SUSTAIN 6 and 3.8 years for LEADER. In the pooled analysis, semaglutide/liraglutide lowered albuminuria from baseline to 2 years after randomization by 24% versus placebo (95% CI, 20%–27%; P <0.001). Significant reductions were also observed in by-trial data analyses ( P <0.001 for all), the largest being with semaglutide 1.0 mg (33% [95% CI, 24%–40%]; P <0.001) at 2 years. With semaglutide 1.0 mg and liraglutide, eGFR slope decline was significantly slowed by 0.87 and 0.26 mL/min/1.73 m 2 /y ( P <0.0001 and P <0.001), respectively, versus placebo. Effects appeared larger in patients with baseline eGFR <60 versus ≥60 mL/min/1.73 m 2 ( P interaction =0.06 and 0.008 for semaglutide 1.0 mg and liraglutide, respectively). Semaglutide/liraglutide significantly lowered risk of persistent 40% and 50% eGFR reductions versus placebo (hazard ratio [HR], 0.86 [95% CI, 0.75–0.99]; P =0.039 and HR, 0.80 [95% CI, 0.66–0.97]; P =0.023, respectively). Similar, nonsignificant, directional results were observed for 30% and 57% eGFR reductions (HR, 0.92 [95% CI, 0.84–1.02]; P =0.10 and HR, 0.89 [95% CI, 0.69–1.13]; P =0.34). In patients with baseline eGFR 30 to <60 mL/min/1.73 m 2, the likelihood of persistent reduction for all thresholds was increased, ranging from HR 0.71 for 30% reduction (95% CI, 0.59–0.85; P =0.0003, P interaction =0.017) to 0.54 for 57% reduction (95% CI, 0.36–0.81; P =0.003, P interaction =0.035). Conclusions: In patients with type 2 diabetes, semaglutide/liraglutide offered kidney-protective effects, which appeared more pronounced in patients with preexisting chronic kidney disease.